Traffic light profiling of meals sold in cafeteria of local universities: A pilot study - Loo, Shi Yee; Md Nazri, Anis Wahida; Rosle, Nur Eizzati Farhani; Ismail, Munirah; Lee, Yi Yi; Krishnasamy, Shanthi (Life Sciences, Medicine and Biomedicine, 2022)
Unregulated university cafeterias may be serving food and beverages high in fat or sugar. Traffic light labelling (TLL) has been able to guide students in making healthier choices. Therefore, the aim of this study was to assess the healthiness level of food and beverages served in university cafeterias by profiling it against TLL and calorie density to evaluate student’s perception towards the implementation of TLL. This pilot observational study was conducted in three universities; two public university and one private institution within Klang Valley. A total of 166 foods and beverages were analysed for calories, fat, saturated fat, sodium, and sugar by using a nutritional software, Nutritionist Pro (TM). Analysed data for each food/beverage were further profiled into TLL and calorie density by using an excel spreadsheet. Food and beverages analysed were those sold in canteen and cafeterias combined those frequently consumed, reported in a food frequency questionnaire (FFQ). A total of 192 students completed a questionnaire containing three sections: personal profile, a short FFQ of their usual intake and their perception towards implementation of TLL in their institutions. 8.1% of all food items were categorised as green (healthy food), whereas 41.9% were amber (moderately healthy food), and 50% were red (unhealthy food). Almost half of the beverages (46.7%) were found to be unhealthy. However, when all foods were profiled for calorie density, more than half (61.8%) were categorised as moderately healthy food. In addition, most of the respondents (88%) showed a positive perception towards the implementation of TLL in the cafeteria. A large number of meals sold in two universities cafeterias were unhealthy and requires dietary modification. TLL implementation was beneficial for tertiary students as it may help guide the students to choose healthier options of cooked meals and packaged foods and beverages.